Catalyst with anti-reverse pole performance and preparation method thereof, preparation method of anode catalyst layer and membrane electrode, and fuel cell

By forming a polymer protective layer on the surface of the carbon support and depositing precious metal nanoparticles, the corrosion problem of the anode catalytic layer of the fuel cell during the reverse polarization process is solved, the anti-reverse polarity performance is improved and the service life of the battery is extended.

CN119208635APending Publication Date: 2024-12-27SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411115828.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The proton exchange membrane fuel cell has a problem of polarization performance attenuation during the reverse polarization process, which leads to corrosion of the anode catalytic layer and structural collapse, affecting the performance of the fuel cell. The existing carbon support method with high graphitization degree has attenuation in the initial polarization performance, and The corrosion rate of carbon support with large specific surface area accelerates during the reverse polarization process.

Method used

Using polymer-covered support method, a polymer protective layer of 1 nm to 100 nm thick is formed on the surface of the carbon support, and precious metal nanoparticles with diameters of 2 nm to 10 nm are deposited on the surface. Anti-reverse reaction is prepared by polymer modification and precious metal precursor reduction reaction. The electrode catalyst improves the stability of the anode catalytic layer.

Benefits of technology

It effectively improves the anti-reverse performance of the fuel cell anode, extends the operating durability of the battery, avoids corrosion and structural damage of the catalyst at high potential, simplifies the preparation process and is easy to control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208635A_ABST
    Figure CN119208635A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst with anti-reverse pole performance and a preparation method thereof, a preparation method of an anode catalyst layer and a membrane electrode, and a fuel cell, the catalyst comprises a carrier and a polymer coating layer formed on the surface of the carrier, and noble metal nanoparticles are attached to the surface of the polymer coating layer; the preparation method comprises the following steps: carrying out polymerization reaction on a polymer monomer, a carrier and an initiator to obtain a polymer modified carrier; performing reduction reaction with a noble metal precursor; the preparation method of the anode catalyst layer and the membrane electrode comprises the following steps: dispersing a catalyst, an oxygen evolution catalyst and a proton conductor in a solvent, coating a proton exchange membrane with the solvent, coating the other side of the proton exchange membrane with a cathode catalyst layer containing a platinum-carbon catalyst and the proton conductor, and configuring a gas diffusion layer; the fuel cell includes a membrane electrode. The preparation method has the beneficial effects that the polymer has relatively good chemical stability under high potential, an internal carrier can be protected, and the anti-pole-reversion performance and the operation durability of the anode of the fuel cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a catalyst with anti-reverse polarity performance and a preparation method thereof, a preparation method of an anode catalyst layer and a membrane electrode, and a fuel cell. Background Art

[0002] With the development of economy and society, energy demand and gap are increasing, but the shortage of fossil energy, environmental pollution and carbon emissions are seriously threatening sustainable development. Hydrogen energy, as a clean energy with zero carbon emissions, is considered to be the ultimate energy source for mankind. Proton exchange membrane fuel cells (PEMFC) have the advantages of high power density, low operating temperature and fast startup, and are considered to be one of the most important and commercial hydrogen energy utilization devices. It is also one of the focuses of international energy science and technology research and development today.

[0003] A fuel cell is a device that can generate electricity by reacting hydrogen and oxygen. In a fuel cell, hydrogen is oxidized to hydrogen ions at the anode and releases electrons, while oxygen is reduced to water at the cathode. These electrons flow through an external circuit to generate electricity. The working principle of fuel cells is simple and efficient, and they do not produce pollutants, so they are widely used in transportation, power systems, and portable devices. However, there is an important problem in the practical application of fuel cells, namely the occurrence of reverse polarity. Reverse polarity refers to the situation when the fuel cell is running, the supply of reactants is insufficient or the discharge of reaction products is not timely, resulting in the performance of the battery being reduced or even stopping working. This may be caused by unstable supply of hydrogen or oxygen, damage or contamination of the electrolyte membrane, blockage of the electrode, etc.

[0004] During the reverse polarity process, for some reason, the hydrogen oxidation reaction (HOR) cannot provide enough protons and electrons. In order to maintain the anode proton flow and electron flow, the anode will undergo oxygen evolution reaction (OER) and carbon oxidation reaction (COR). The two compete with each other. At this time, the potential of the anode will be higher than that of the cathode, causing the reverse polarity phenomenon. Although COR has a lower thermodynamic potential, its kinetic rate is slow. Therefore, OER is the main reaction at low reverse polarity potential. After OER cannot provide enough protons and electrons, COR turns into a dominant reaction, which leads to corrosion of the catalyst layer and collapse of the structure, affecting the performance of the fuel cell. Therefore, the key step to protect the structure of the catalyst layer is to improve the stability of the anode catalyst layer at high potential, that is, to improve the anti-oxidation and high potential corrosion resistance of the carbon carrier. Some researchers use carbon carriers with a high degree of graphitization as anode catalyst carriers, and use their better anti-oxidation ability to improve the anti-reverse polarity of the anode catalyst layer. However, this method usually leads to the attenuation of the initial polarization performance, which is not conducive to the application in the whole battery. In addition, for a large specific surface area (greater than 1000m 2 / g) of carbon carrier, since the exposed area of ​​the carbon carrier is relatively larger, the corrosion rate will be further accelerated, and the polarization performance will decay more significantly during the reverse polarity process. Summary of the invention

[0005] In view of the problem that the polarization performance of existing proton exchange membrane fuel cells decays rapidly in the reverse electrode, the purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a catalyst with anti-reverse polarity performance and a preparation method thereof, a method for preparing an anode catalyst layer and a membrane electrode, and a fuel cell.

[0006] The technical solution of the present invention is as follows:

[0007] A first aspect of the present invention provides a catalyst with anti-reverse polarity performance, comprising a carrier and a polymer coating layer formed on the surface of the carrier, wherein precious metal nanoparticles are attached to the surface of the polymer coating layer.

[0008] Preferably, the thickness of the polymer coating layer is 1 nm to 100 nm, and the polymer includes one or more of polypyrrole, polyaniline, polythiophene and poly(p-phenylene vinylene).

[0009] Preferably, the diameter of the noble metal nanoparticles is 2nm to 10nm, the loading amount of the noble metal nanoparticles is 10wt% to 70wt%, and the noble metal nanoparticles include one or more of platinum, iridium, ruthenium, and rhodium nanoparticles;

[0010] The carrier is a carbon carrier, the particle size of the carbon carrier is 30nm to 50nm, and the specific surface area of ​​the carbon carrier is 20m 2 / g~2000m 2 / g, the carbon carrier includes one or more of acetylene black, carbon nanotubes, carbon nanofibers, graphene, and Ketjen black.

[0011] A second aspect of the present invention provides a method for preparing a catalyst having anti-reverse polarity performance, comprising the following steps:

[0012] The polymer monomer is mixed with the carrier, and an initiator is added to cause a polymerization reaction to obtain a polymer-modified carrier;

[0013] The polymer modified carrier is subjected to reduction reaction with a noble metal precursor to obtain a catalyst.

[0014] Preferably, the polymer monomers include one or more of pyrrole, aniline, thiophene, and p-styrene;

[0015] The polymerization initiator includes one or more of ferric chloride, hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, and methyl ethyl ketone peroxide;

[0016] The noble metal precursor includes one or more of platinum, iridium, ruthenium, and rhodium precursors;

[0017] The feed mass ratio of the polymer monomer to the carrier is 1:1 to 1:5, and the feed molar ratio of the polymer monomer to the polymerization initiator is 4:1 to 1:4;

[0018] The feed mass ratio of the noble metal precursor to the carrier is 1:9 to 9:1.

[0019] Preferably, the method specifically comprises the following steps:

[0020] The polymer monomer and the carbon carrier are dispersed in a solvent, acidified and stirred evenly, a polymerization initiator is added dropwise and stirred, and the solid-liquid separation and drying are performed to obtain a polymer-coated carbon carrier;

[0021] The polymer-coated carbon carrier is dispersed in a reducing agent, and then a noble metal salt is added and heated to reflux, and then the temperature is reduced and then acidified, and then the solid-liquid separation is performed and then washed and dried to obtain the catalyst.

[0022] Preferably, the noble metal salt includes one or more of chlorate, chloride, and acetylacetonate, and the feed concentration of the noble metal salt is 0.01 to 1 mg / mL;

[0023] The reducing agent includes one or more of formic acid, sodium borohydride, ethanol, hydrogen peroxide, and ethylene glycol;

[0024] The solvent includes one or more of water, ethanol, isopropanol, n-propanol, cyclohexane, acetone, and methanol;

[0025] The heating temperature is 120 to 200 degrees Celsius, and the heating time is 1 to 15 hours.

[0026] A third aspect of the present invention provides a method for preparing an anode catalyst layer, comprising the following steps:

[0027] Dispersing the above catalyst or the catalyst prepared by the above method, an oxygen evolution catalyst and a proton conductor in a catalyst slurry solvent, and coating the mixture on a proton exchange membrane after uniform dispersion to obtain an anode catalyst layer;

[0028] Wherein, the oxygen evolution catalyst includes one or more of iridium dioxide, ruthenium dioxide, metallic iridium, and rhodium dioxide;

[0029] The proton conductor includes one or more of Nafion D520, Nafion D2020, and Aquivion D79-25BS;

[0030] The catalyst slurry solvent includes one or more of ethanol, isopropanol, water, methanol, and ethylene glycol;

[0031] The proton exchange membrane includes one or more of Nafion NR211, Nafion NR212, Gore M850.15, and Gore M735.18.

[0032] A fourth aspect of the present invention provides a method for preparing a membrane electrode, comprising the following steps:

[0033] The other side of the proton exchange membrane coated with the anode catalyst layer is coated with a cathode catalyst layer comprising a platinum-carbon catalyst and a proton conductor, and a gas diffusion layer is disposed outside the anode catalyst layer and the cathode catalyst layer to obtain a membrane electrode;

[0034] Wherein, the platinum-carbon catalyst includes one or more of Tanaka TEC10EA50E, Tanaka TEC10EA40E, TanakaTEC10V50E, Johnson Matthey HiSPEC 13100, and Johnson Matthey HiSPEC 9100;

[0035] The proton conductor includes one or more of Nafion D520, Nafion D2020, and Aquivion D79-25BS;

[0036] The gas diffusion layer includes one or more of Avcarb MB30, Sigracet 22BB, Sigracet 35BB, and AvcarbGDS3250.

[0037] A fifth aspect of the present invention provides a fuel cell, comprising a membrane electrode prepared by the above-mentioned preparation method.

[0038] The present invention has at least one of the following beneficial effects:

[0039] 1. The present invention adopts a method of coating the carrier with a polymer to form a polymer protective layer on the surface of the carrier. Since the polymer has relatively good chemical stability at high potential, it can protect the internal carrier and isolate the carrier from the external oxidation and corrosion environment, so that the catalyst has better structural tolerance under the reverse polarity. The preparation method of the present invention first polymerizes on the surface of the carbon carrier and then deposits it. The preparation method is simple and easy to control.

[0040] 2. The fuel cell prepared by using the anti-reverse polarity anode catalyst of the present invention can effectively improve the anti-reverse polarity performance of the fuel cell anode and improve the operating durability of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a flow chart for preparing the anode catalyst layer provided by the present invention;

[0042] Figure 2 This is a TEM image of a polyaniline-modified Vulcan XC-72R carbon support provided in Example 1 of the present invention;

[0043] Figure 3 This is a TEM image of the platinum catalyst supported by polyaniline-modified Vulcan XC-72R carbon powder provided in Example 1 of the present invention;

[0044] Figure 4 This is a polarization curve of the polyaniline-modified Vulcan XC-72R carbon powder-supported platinum catalyst assembled membrane electrode provided in Example 1 of the present invention;

[0045] Figure 5 This is a graph showing the anti-reverse polarity test results of the polyaniline-modified Vulcan XC-72R carbon powder-supported platinum catalyst assembled membrane electrode provided in Example 1 of the present invention;

[0046] Figure 6 This is a polarization curve of the Vulcan XC-72R carbon powder-loaded platinum catalyst assembled membrane electrode provided in Comparative Example 1 of the present invention;

[0047] Figure 7 This is a graph showing the anti-reverse polarity test results of the Vulcan XC-72R carbon powder-loaded platinum catalyst assembled membrane electrode provided in Comparative Example 1 of the present invention;

[0048] Figure 8 This is a polarization curve of a membrane electrode assembled with a platinum catalyst supported by a small amount of polyaniline-modified Vulcan XC-72R carbon powder provided in Comparative Example 2 of the present invention;

[0049] Fig. 9 This is a graph showing the anti-reverse polarity test result of a membrane electrode assembled with a platinum catalyst supported by a small amount of polyaniline-modified Vulcan XC-72R carbon powder provided in Comparative Example 2 of the present invention;

[0050] Fig.10 This is a polarization curve of a membrane electrode assembled with a platinum catalyst supported by a large amount of polyaniline-modified Vulcan XC-72R carbon powder provided in Comparative Example 3 of the present invention;

[0051] Fig.11 This is the result of the anti-reverse polarity test of the membrane electrode assembled with a large amount of polyaniline modified Vulcan XC-72R carbon powder loaded with platinum catalyst provided in Comparative Example 3 of the present invention

[0052] Fig.12 This is a polarization curve diagram of a membrane electrode assembled with platinum catalyst supported by polyaniline-modified Ketjenblack EC-600JD carbon powder provided in Example 2 of the present invention;

[0053] Fig.13This is a graph showing the anti-reverse polarity test results of the polyaniline-modified Ketjenblack EC-600JD carbon powder-loaded platinum catalyst assembled membrane electrode provided in Example 2 of the present invention;

[0054] Fig.14 This is a polarization curve of the platinum catalyst assembled membrane electrode supported by Ketjenblack EC-600JD carbon powder provided in Comparative Example 4 of the present invention;

[0055] Fig.15 This is a graph showing the anti-reverse polarity test results of the platinum catalyst assembled membrane electrode loaded with Ketjenblack EC-600JD carbon powder provided in Comparative Example 4 of the present invention;

[0056] Fig.16 This is a polarization curve of a membrane electrode assembled with a platinum catalyst supported by polypyrrole-modified Vulcan XC-72R carbon powder provided in Example 3 of the present invention;

[0057] Fig.17 This is a graph showing the anti-reverse polarity test results of the polypyrrole-modified Vulcan XC-72R carbon powder-loaded platinum catalyst assembled membrane electrode provided in Example 3 of the present invention;

[0058] Fig.18 This is a polarization curve of a membrane electrode assembled with a small amount of polypyrrole-modified Vulcan XC-72R carbon powder loaded with platinum catalyst provided in Comparative Example 5 of the present invention;

[0059] Fig.19 This is a graph showing the anti-reverse polarity test result of a membrane electrode assembled with a small amount of polypyrrole-modified Vulcan XC-72R carbon powder loaded with platinum catalyst provided in Comparative Example 5 of the present invention;

[0060] Fig. 20 This is a polarization curve of a membrane electrode assembled with a platinum catalyst supported by a large amount of polypyrrole-modified Vulcan XC-72R carbon powder provided in Comparative Example 6 of the present invention;

[0061] Fig.21 This is a graph showing the anti-reverse polarity test results of a membrane electrode assembled with a platinum catalyst loaded with a large amount of polypyrrole-modified Vulcan XC-72R carbon powder provided in Comparative Example 6 of the present invention. DETAILED DESCRIPTION

[0062] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0063] An embodiment of the present invention provides a catalyst with anti-reverse polarity performance, including a carrier and a polymer coating layer formed on the surface of the carrier, wherein noble metal nanoparticles are attached to the surface of the polymer coating layer.

[0064] The present invention forms a polymer protective layer on the surface of the carbon carrier. Since the polymer has relatively good chemical stability at high potential, it can protect the internal carbon carrier and isolate the carbon carrier from the external oxidation and corrosion environment, so that the catalyst of the present invention has better structural tolerance under reverse polarity conditions.

[0065] In some embodiments, in the polymer-modified carbon carrier, the polymer coating thickness is 1 nm to 100 nm; preferably 1 nm to 90 nm; more preferably 1 nm to 80 nm; further preferably 1 nm to 70 nm; further more preferably 1 nm to 50 nm.

[0066] The polymer coating thickness needs to be thin enough to allow the catalyst particles to contact the reactants and avoid affecting the catalytic performance.

[0067] In some embodiments, the polymer includes polypyrrole, polyaniline, polythiophene, poly(p-phenylene vinylene).

[0068] In some embodiments, the carrier is a carbon carrier, and the particle size of the carbon carrier is 30 nm to 50 nm, preferably 34 nm to 46 nm, and more preferably 38 nm to 42 nm.

[0069] In some embodiments, the specific surface area of ​​the carbon support is 20 m 2 / g~2000m 2 / g; preferably 200m 2 / g~1800m 2 / g; more preferably 500m 2 / g~1500m 2 / g; more preferably 700m 2 / g~1200m 2 / g.

[0070] In some embodiments, the noble metal nanoparticles include one or more of platinum, iridium, ruthenium, and rhodium nanoparticles; in some embodiments, the diameter of the noble metal nanoparticles is 2 to 10 nm, and the loading of the noble metal nanoparticles is 10 wt% to 70 wt%. Preferably, the diameter of the noble metal nanoparticles is 3 to 9 nm, and the loading of the noble metal nanoparticles is 20 wt% to 60 wt%; more preferably, the diameter of the noble metal nanoparticles is 4 to 8 nm, and the loading of the noble metal nanoparticles is 30 wt% to 50 wt%; more preferably, the diameter of the noble metal nanoparticles is 5 to 7 nm, and the loading of the noble metal nanoparticles is 35 wt% to 45 wt%.

[0071] In some embodiments, the noble metal nanoparticles include one or more of platinum, iridium, ruthenium, and rhodium nanoparticles.

[0072] Another embodiment of the present invention provides a method for preparing a catalyst having anti-reverse polarity performance, comprising the following steps:

[0073] The polymer monomer is mixed with the carrier, and an initiator is added to cause a polymerization reaction to obtain a polymer-modified carrier;

[0074] The polymer modified carrier is subjected to reduction reaction with a noble metal precursor to obtain a catalyst.

[0075] The method for preparing a catalyst for improving the anti-reverse polarity performance of a fuel cell anode by coating a carrier with a polymer in the embodiment of the present application uses a polymer to form a coating layer on the carrier, and deposits precious metal nanoparticles on its surface. The polymer is polymerized in situ on the surface of the carbon carrier, and the thickness of the coating layer can be controlled by controlling the amount of the polymer to avoid the coating layer being too thick and having an adverse effect on the catalytic performance. At the same time, the polymer-modified carrier has uniform surface properties, which is conducive to the uniform deposition of precious metal nanoparticles.

[0076] See also Figure 1 As shown, in a first embodiment of the present invention, the coating process includes the following operations:

[0077] After the polymer monomer and the carbon carrier are uniformly dispersed, an initiator is added to cause the polymer monomer to undergo a polymerization reaction, thereby coating a layer of polymer on the surface of the carbon carrier to obtain a polymer-modified carbon carrier;

[0078] In a specific embodiment of the present invention, the coating treatment specifically includes: dispersing the polymer monomer and the carbon carrier in a solvent, stirring evenly after acidification, adding a polymerization initiator dropwise and stirring at low temperature, and drying after solid-liquid separation to obtain the polymer-coated carbon carrier.

[0079] See also Figure 1 As shown, in the first embodiment of the present invention, the catalyst deposition comprises the following operations:

[0080] The modified carbon carrier and the noble metal precursor are mixed evenly and then reduced in a liquid phase, and the noble metal is deposited on the surface of the modified carbon carrier to obtain a noble metal catalyst supported by the modified carbon carrier and used for the anode of a fuel cell.

[0081] In a specific embodiment of the present invention, the catalyst deposition specifically includes: dispersing the polymer-coated carbon carrier in a reducing agent, heating to reflux after adding a precious metal salt, acidifying after cooling to deposit the precious metal on the surface of the polymer-coated carbon carrier, washing and drying after solid-liquid separation to obtain the precious metal catalyst loaded on the polymer-coated carbon carrier.

[0082] In this embodiment, the polymer monomer is first mixed with the carbon carrier and evenly distributed on the surface of the carbon carrier to provide conditions for the subsequent uniform distribution of the polymer. At the same time, the addition rate of the initiator should be controlled, and a peristaltic pump or dropper can be used for dropwise addition. At the same time, the reaction system needs to be kept at a low temperature to avoid excessive polymerization resulting in uneven distribution of the polymer.

[0083] In the above embodiment, if necessary, the reaction system may be stirred or subjected to ultrasonic dispersion treatment to improve the reaction efficiency and particle dispersibility.

[0084] In some embodiments, the solvent includes one or more of water, ethanol, isopropanol, n-propanol, cyclohexane, acetone, and methanol.

[0085] In some embodiments, the feed mass ratio of the polymer monomer to the carbon carrier is (1:1) to (1:5), and the feed molar ratio of the polymer monomer to the polymerization initiator is (4:1) to (1:4).

[0086] Preferably, the feed mass ratio of the polymer monomer to the carbon carrier is (1:2) to (1:4), and the feed molar ratio of the polymer monomer to the polymerization initiator is (3:1) to (1:3).

[0087] More preferably, the feed mass ratio of the polymer monomer to the carbon carrier is (1:2.5) to (1:3.5), and the feed molar ratio of the polymer monomer to the polymerization initiator is (2:1) to (1:2).

[0088] In different embodiments, the feed mass ratio of the polymer monomer to the carbon carrier is (1:1), (1:2), (1:3), (1:4) or (1:5); the feed molar ratio of the polymer monomer to the polymerization initiator is (1:4), (1:3), (1:2), (1:1), (2:1), (3:1) or (4:1).

[0089] In some embodiments, the mass ratio of the precious metal precursor to the carbon carrier is (1:9) to (9:1); preferably (1:7) to (7:1); and more preferably (1:5) to (5:1).

[0090] In different embodiments, the mass ratio of the precious metal precursor to the carbon carrier is (1:1), (1:1.5), (1:2), (1.5:1) or (2:1).

[0091] In some embodiments, the polymer monomers include one or more of pyrrole, aniline, thiophene, and p-phenylene glycol.

[0092] In some embodiments, the carbon support includes one or more of acetylene black, carbon nanotubes, carbon nanofibers, graphene, and Ketjen black.

[0093] In some embodiments, the polymerization initiator includes one or more of ferric chloride, hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, and methyl ethyl ketone peroxide.

[0094] In some embodiments, the reduction temperature is 120 to 200 degrees Celsius, and the reduction time is 1 to 15 hours. Preferably, the reduction temperature is 140 to 180 degrees Celsius, and the reduction time is 5 to 12 hours. More preferably, the reduction temperature is 150 to 170 degrees Celsius, and the reduction time is 7 to 10 hours.

[0095] In some embodiments, the feed concentration of the noble metal salt is 0.01-1 mg / mL, and the feed concentration in this embodiment refers to "the ratio of the added mass of the noble metal salt to the added volume of the reducing agent". Preferably, the feed concentration is 0.1-0.9 mg / mL; more preferably, the feed concentration is 0.3-0.7 mg / mL.

[0096] In different embodiments, the reduction temperature can be 120 degrees Celsius, 140 degrees Celsius, 160 degrees Celsius, 180 degrees Celsius or 200 degrees Celsius; the reduction time is 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 8 hours, 10 hours, 12 hours, 13 hours, 14 hours or 15 hours; the feed concentration of the precious metal salt is 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL or 1 mg / mL.

[0097] In some embodiments, the precious metal includes one or more of platinum, iridium, ruthenium, and rhodium.

[0098] In some embodiments, the noble metal salt includes one or more of chlorate, chloride, and acetylacetonate.

[0099] In some embodiments, the reducing agent includes one or more of formic acid, sodium borohydride, ethanol, hydrogen peroxide, and ethylene glycol.

[0100] Another embodiment of the present invention provides a method for preparing an anode catalyst layer, comprising the following steps:

[0101] The catalyst prepared by the above method or the above catalyst, oxygen evolution catalyst and proton conductor are dispersed in a catalyst slurry solvent, and coated on a proton exchange membrane after uniform dispersion to obtain an anode catalyst layer.

[0102] The preparation method can improve the utilization rate of the anode catalyst layer, reduce the contact resistance between the anode catalyst layer and the proton exchange membrane, and improve the battery performance.

[0103] In some embodiments, the oxygen evolution catalyst includes one or more of iridium dioxide, ruthenium dioxide, metallic iridium, and rhodium dioxide.

[0104] In some embodiments, the proton conductor includes one or more of Nafion D520, Nafion D2020, and Aquivion D79-25BS.

[0105] In some embodiments, the catalyst slurry solvent includes one or more of ethanol, isopropanol, water, methanol, and ethylene glycol.

[0106] In some embodiments, the proton exchange membrane includes one or more of Nafion NR211, Nafion NR212, Gore M850.15, and Gore M735.18.

[0107] Another embodiment of the present invention provides a method for preparing a membrane electrode, comprising the following steps:

[0108] The other side of the proton exchange membrane coated with the anode catalyst layer is coated with a cathode catalyst layer containing a platinum-carbon catalyst and a proton conductor, and a gas diffusion layer is arranged outside the anode catalyst layer and the cathode catalyst layer to obtain a membrane electrode.

[0109] The preparation method can optimize gas distribution, reduce the contact resistance between the anode catalyst layer and the gas diffusion layer, and improve battery performance.

[0110] In some embodiments, the platinum-carbon catalyst includes one or more of Tanaka TEC10EA50E, Tanaka TEC10EA40E, Tanaka TEC10V50E, Johnson Matthey HiSPEC 13100, and Johnson Matthey HiSPEC 9100.

[0111] In some embodiments, the proton conductor includes one or more of Nafion D520, Nafion D2020, and Aquivion D79-25BS;

[0112] In some embodiments, the gas diffusion layer includes one or more of Avcarb MB30, Sigracet 22BB, Sigracet35BB, and Avcarb GDS3250.

[0113] The last embodiment of the present invention provides a fuel cell, comprising a membrane electrode, wherein the membrane electrode is a membrane electrode prepared by the above-mentioned preparation method.

[0114] The fuel cell prepared by using the anti-reverse polarity anode catalyst of the present invention can effectively improve the anti-reverse polarity performance of the fuel cell anode and improve the operating durability of the fuel cell.

[0115] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.

[0116] Example 1

[0117] This example is used to illustrate a catalyst disclosed in the present invention for improving the anti-reverse polarity performance of a fuel cell anode by a polymer-coated carbon carrier and a preparation method thereof, comprising the following steps:

[0118] Step 1. Disperse Vulcan XC-72R carbon powder (20 mg) in 100 mL of ethanol, stir and sonicate for 1 hour, add 3 mL of concentrated sulfuric acid and 15 uL of aniline monomer, sonicate for another 1 hour, and stir for 12 hours.

[0119] Step 2. Disperse 50 mg of ammonium persulfate in 100 mL of 0.5 M sulfuric acid, add dropwise to the carbon powder dispersion, place in an ice bath for 10 hours, vacuum filter, wash, and vacuum dry at 80 degrees Celsius for 12 hours to obtain polyaniline-modified Vulcan XC-72R carbon powder.

[0120] Step 3. Chloroplatinic acid (20 mg) and the above-mentioned polyaniline-modified Vulcan XC-72R carbon powder (10 mg) were added to 250 mL of ethylene glycol, stirred for 12 hours, heated to reflux at 200 degrees Celsius for 10 hours, and then naturally cooled, 8 mL of 0.5 M sulfuric acid was added. The mixture was washed after vacuum filtration and dried at 60 degrees Celsius for 12 hours to obtain a polyaniline-modified Vulcan XC-72R carbon powder-supported platinum catalyst.

[0121] Step 4. Add the above 4 mg polyaniline-modified Vulcan XC-72R carbon powder-supported platinum catalyst, 2 mg iridium dioxide and 20 uL Nafion D520 into 2 mL isopropanol, ultrasonically stir for 1.5 hours, and ultrasonically spray onto the Nafion NR211 proton exchange membrane to obtain a proton exchange membrane coated with an anode catalyst layer.

[0122] Step 5. Add 8 mg Tanaka TEC10EA50E and 40 uL Nafion D520 to 5 mL isopropanol, ultrasonically stir for 1.5 hours, and ultrasonically spray coat the other side of the proton exchange membrane coated with the anode catalyst layer, and configure Avcarb MB30 gas diffusion layers on the outside of the catalyst layers on both sides to obtain the membrane electrode.

[0123] The Vulcan XC-72R powder modified with polyaniline was observed by electron microscopy, and the results were as follows: Figure 2 ,Depend on Figure 2 It can be seen that polyaniline is coated on the surface of the Vulcan XC-72R carbon support to form a uniformly covered amorphous coating layer.

[0124] Electron microscopy observation of polyaniline modified Vulcan XC-72R carbon powder supported platinum catalyst powder showed the following results: Figure 3 ,Depend on Figure 3 It can be seen that platinum nanoparticles with uniform particle size are evenly distributed on the polyaniline-modified Vulcan XC-72R.

[0125] The polarization performance and anti-reverse polarity performance of the obtained membrane electrode were tested.

[0126] The full battery system was used to test the membrane electrode polarization performance curve, with the platinum loading of the anode and cathode being 0.4 mg / cm -2 and 0.1mg / cm -2 , the battery temperature is 80 degrees Celsius, the relative humidity is 100%, the back pressure is 100kPa, the hydrogen and air gas flow rates are 0.5L / min and 1L / min respectively, and the polarization curves are as follows Figure 4 The anti-reverse polarity performance test method is to change the anode gas to nitrogen, maintain a constant current density, and observe the time to reach the cut-off voltage. The test conditions are 100% relative humidity, no back pressure, and the nitrogen and air gas flow rates are 0.4L / min and 0.2L / min respectively. The test results are shown in Figure 5 shown.

[0127] Comparative Example 1

[0128] This comparative example provides an anode catalyst without polymer coating, including most of the operating steps in Example 1, except that:

[0129] The carbon support was not modified by coating Vulcan XC-72R with polyaniline.

[0130] The obtained membrane electrode was tested for polarization performance and anti-reverse polarity performance, and the obtained polarization curve is as follows: Figure 6 As shown, the anti-reverse polarity test results are as follows Figure 7 shown.

[0131] Comparative Example 2

[0132] This comparative example provides an anode catalyst coated with a small amount of polymer, including most of the operating steps in Example 1, except that:

[0133] The amount of aniline monomer added was 2uL.

[0134] The obtained membrane electrode was tested for polarization performance and anti-reverse polarity performance, and the obtained polarization curve is as follows: Figure 8As shown, the anti-reverse polarity test results are as follows Fig. 9 shown.

[0135] Comparative Example 3

[0136] This comparative example provides an anode catalyst coated with a large amount of polymer, including most of the operating steps in Example 1, except that:

[0137] The amount of aniline monomer added was 50uL.

[0138] The membrane electrodes obtained in the above comparative examples 2 to 3 were tested for polarization performance and anti-reverse polarity performance, and the obtained polarization curves are as follows: Fig.10 As shown, the anti-reverse polarity test results are as follows Fig.11 shown.

[0139] Example 2

[0140] This example is used to illustrate a catalyst disclosed in the present invention for improving the anti-reverse polarity performance of anode of a fuel cell by using a polymer-coated carbon carrier and a preparation method thereof, and includes most of the operation steps in Example 1, except that:

[0141] The carbon carrier used was Ketjenblack EC-600JD from Akzo Nobel Chemicals.

[0142] The obtained membrane electrode was tested for polarization performance and anti-reverse polarity performance, and the obtained polarization curve is as follows: Fig.12 As shown, the anti-reverse polarity test results are as follows Fig.13 shown.

[0143] Comparative Example 4

[0144] This comparative example provides an anode catalyst without polymer coating, including most of the operating steps in Example 2, except that:

[0145] The carbon support was not modified by coating Ketjenblack EC-600JD with polyaniline.

[0146] The obtained membrane electrode was tested for polarization performance and anti-reverse polarity performance, and the obtained polarization curve is as follows: Fig.14 As shown, the anti-reverse polarity test results are as follows Fig.15 shown.

[0147] Through the above Figures 4 to 15It can be seen from the test results that the membrane electrode assembled with the platinum catalyst supported by the polyaniline modified carbon carrier prepared by the preparation method of the present application has a longer anti-reverse time than the membrane electrode assembled with the uncoated catalyst. For the Vulcan XC-72R carrier, the anti-reverse time is extended by 16 times, and for Ketjenblack EC-600JD, the anti-reverse time is extended by 8 times. It can also be seen that the membrane electrode assembled with the platinum catalyst supported by the polyaniline modified carbon carrier prepared in Example 1 has a longer anti-reverse time than the membrane electrode assembled in Comparative Examples 2 to 3. This is because the polymer coating layer in Comparative Example 2 is too thin. If the polymer coating layer is too thin, there will be problems such as uneven coating or poor isolation effect; and the polymer coating layer in Comparative Example 3 is too thick. If the polymer coating layer is too thick, there will be problems such as affecting electronic conduction and encapsulating catalyst particles. After a lot of research, the applicant found that the polymer coating layer is most suitable for 1 to 100 nm.

[0148] Example 3

[0149] This example is used to illustrate a catalyst disclosed in the present invention for improving the anti-reverse polarity performance of a fuel cell anode by a polymer-coated carbon carrier and a preparation method thereof, comprising the following steps:

[0150] Step 1. Disperse Vulcan XC-72R carbon powder (20 mg) in 100 mL of ethanol, stir and sonicate for 1 hour, add 3 mL of concentrated sulfuric acid and 15 uL of pyrrole monomer, sonicate for another 1 hour, and stir for 12 hours.

[0151] Step 2. Disperse 50 mg of ammonium persulfate in 100 mL of 0.5 M sulfuric acid, add dropwise to the carbon powder dispersion, place in an ice bath for 10 hours, vacuum filter, wash, and vacuum dry at 80 degrees Celsius for 12 hours to obtain polypyrrole-modified Vulcan XC-72R carbon powder.

[0152] Step 3. Chloroplatinic acid (20 mg) and the above-mentioned polypyrrole-modified Vulcan XC-72R carbon powder (10 mg) were added to 250 mL of ethylene glycol, stirred for 12 hours, heated to reflux at 200 degrees Celsius for 10 hours, and then naturally cooled, 8 mL of 0.5 M sulfuric acid was added. The mixture was washed after vacuum filtration and dried at 60 degrees Celsius for 12 hours to obtain a polyaniline-modified Vulcan XC-72R carbon powder-loaded platinum catalyst.

[0153] The other steps are the same as those in Example 1.

[0154] The obtained membrane electrode was tested for polarization performance and anti-reverse polarity performance, and the obtained polarization curve is as follows: Fig.16 As shown, the anti-reverse polarity test results are as follows Fig.17 shown.

[0155] Comparative Example 5

[0156] This comparative example provides an anode catalyst coated with a small amount of polymer, including most of the operating steps in Example 3, except that:

[0157] The amount of pyrrole monomer added was 3uL.

[0158] The membrane electrode obtained in the above comparative example 5 was tested for polarization performance and anti-reverse polarity performance, and the obtained polarization curve is as follows: Fig.18 As shown, the anti-reverse polarity test results are as follows Fig.19 shown.

[0159] Comparative Example 6

[0160] This comparative example provides an anode catalyst coated with a large amount of polymer, including most of the operating steps in Example 3, except that:

[0161] The amount of pyrrole monomer added was 60uL.

[0162] The membrane electrode obtained in the above comparative example 6 was tested for polarization performance and anti-reverse polarity performance, and the obtained polarization curve is as follows: Fig. 20 As shown, the anti-reverse polarity test results are as follows Fig.21 shown.

[0163] Through the above Figure 16-21 It can be seen from the test results that the membrane electrode assembled with the platinum catalyst loaded on the polypyrrole-modified carbon carrier obtained by the preparation method of the present application has a longer anti-reverse polarity time compared with the membrane electrode assembled with the uncoated catalyst, but too thick or too thin coating thickness will still lead to the deterioration of polarization performance and anti-reverse polarity performance.

[0164] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A catalyst having anti-reverse polarity performance, characterized in that: The invention comprises a carrier and a polymer coating layer formed on the surface of the carrier, wherein noble metal nanoparticles are attached to the surface of the polymer coating layer.

2. The catalyst according to claim 1, characterized in that The thickness of the polymer coating layer is 1 nm to 100 nm, and the polymer includes one or more of polypyrrole, polyaniline, polythiophene and poly(p-phenylene vinylene).

3. The catalyst according to claim 1, characterized in that The diameter of the noble metal nanoparticles is 2nm to 10nm, the loading amount of the noble metal nanoparticles is 10wt% to 70wt%, and the noble metal nanoparticles include one or more of platinum, iridium, ruthenium, and rhodium nanoparticles; The carrier is a carbon carrier, the particle size of the carbon carrier is 30nm to 50nm, and the specific surface area of ​​the carbon carrier is 20m 2 / g~2000m 2 / g, the carbon carrier includes one or more of acetylene black, carbon nanotubes, carbon nanofibers, graphene, and Ketjen black.

4. A method for preparing a catalyst having anti-reverse polarity performance as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: The polymer monomer is mixed with the carrier, and an initiator is added to cause a polymerization reaction to obtain a polymer-modified carrier; The polymer modified carrier is subjected to reduction reaction with a noble metal precursor to obtain a catalyst.

5. The preparation method according to claim 4, characterized in that: The polymer monomers include one or more of pyrrole, aniline, thiophene, and p-styrene; The polymerization initiator includes one or more of ferric chloride, hydrogen peroxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, and methyl ethyl ketone peroxide; The noble metal precursor includes one or more of platinum, iridium, ruthenium, and rhodium precursors; The feed mass ratio of the polymer monomer to the carrier is 1:1 to 1:5, and the feed molar ratio of the polymer monomer to the polymerization initiator is 4:1 to 1:4; The feed mass ratio of the noble metal precursor to the carrier is 1:9 to 9:

1.

6. The preparation method according to claim 4, characterized in that: The following steps are involved: The polymer monomer and the carbon carrier are dispersed in a solvent, acidified and stirred evenly, a polymerization initiator is added dropwise and stirred, and the solid-liquid separation and drying are performed to obtain a polymer-coated carbon carrier; The polymer-coated carbon carrier is dispersed in a reducing agent, and then a noble metal salt is added and heated to reflux, and then the temperature is reduced and then acidified, and then the solid-liquid separation is performed and then washed and dried to obtain the catalyst.

7. The preparation method according to claim 6, characterized in that: The noble metal salt includes one or more of chlorate, chloride, and acetylacetonate, and the feed concentration of the noble metal salt is 0.01 to 1 mg / mL; The reducing agent includes one or more of formic acid, sodium borohydride, ethanol, hydrogen peroxide and ethylene glycol; The solvent includes one or more of water, ethanol, isopropanol, n-propanol, cyclohexane, acetone and methanol; The heating temperature is 120 to 200 degrees Celsius, and the heating time is 1 to 15 hours.

8. A method for preparing an anode catalyst layer, characterized in that: The following steps are involved: Dispersing the catalyst described in any one of claims 1 to 3 or the catalyst prepared by the method described in any one of claims 4 to 7, an oxygen evolution catalyst, and a proton conductor in a catalyst slurry solvent, and coating the dispersed catalyst on a proton exchange membrane to obtain an anode catalyst layer; Wherein, the oxygen evolution catalyst includes one or more of iridium dioxide, ruthenium dioxide, metallic iridium, and rhodium dioxide; The proton conductor includes one or more of Nafion D520, Nafion D2020, and Aquivion D79-25BS; The catalyst slurry solvent includes one or more of ethanol, isopropanol, water, methanol, and ethylene glycol; The proton exchange membrane includes one or more of Nafion NR211, Nafion NR212, Gore M850.15, and Gore M735.

18.

9. A method for preparing a membrane electrode, characterized in that: The following steps are involved: Coating the other side of the proton exchange membrane coated with the anode catalyst layer prepared by the method of claim 8 with a cathode catalyst layer comprising a platinum-carbon catalyst and a proton conductor, and configuring a gas diffusion layer outside the anode catalyst layer and the cathode catalyst layer to obtain a membrane electrode; Wherein, the platinum-carbon catalyst includes one or more of Tanaka TEC10EA50E, Tanaka TEC10EA40E, TanakaTEC10V50E, Johnson Matthey HiSPEC 13100, and Johnson Matthey HiSPEC 9100; The proton conductor includes one or more of Nafion D520, Nafion D2020, and Aquivion D79-25BS; The gas diffusion layer includes one or more of Avcarb MB30, Sigracet 22BB, Sigracet 35BB, and Avcarb GDS3250.

10. A fuel cell, characterized in that: It comprises a membrane electrode prepared by the preparation method according to claim 9.